2013
DOI: 10.1371/journal.pone.0061791
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in the HN and SH Genes of Mumps Viruses: A Comparison of Strains from Mumps Cases with and without Neurological Symptoms

Abstract: BackgroundIt is known that mumps virus (MuV) strains may vary in their neurovirulent capacity, and certain MuV strains may be highly neurotropic. In animal models and epidemiological studies, mutations at specific amino acids (aa) have been proposed to be associated with neurovirulence. To assess whether these genetic variations can be observed in clinical samples from patients and if they correlate with neurovirulence as determined by clinical symptoms, 39 mumps patients with or without neurological symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Accordingly, the Urabe AM9's use as a vaccine strain was discontinued in Japan, Canada, and the United Kingdom. [19] Based on these facts, it seems that the mumps vaccine strain may need an alteration in Iran to achieve better immunization after vaccination. Previous studies have indicated that amino acid substitutions at positions 335, 354, 356, 360, 464, and 466 in the HN region, and in positions 29 and 48 in the SH region, resulted in neuro-virulence of the virus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Accordingly, the Urabe AM9's use as a vaccine strain was discontinued in Japan, Canada, and the United Kingdom. [19] Based on these facts, it seems that the mumps vaccine strain may need an alteration in Iran to achieve better immunization after vaccination. Previous studies have indicated that amino acid substitutions at positions 335, 354, 356, 360, 464, and 466 in the HN region, and in positions 29 and 48 in the SH region, resulted in neuro-virulence of the virus.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that amino acid substitutions at positions 335, 354, 356, 360, 464, and 466 in the HN region, and in positions 29 and 48 in the SH region, resulted in neuro-virulence of the virus. [19,42,43] The HN region is the main immunogenic part of the mumps genome and contains glycosylation sites in 3 epitope domains (aa265-288, aa329-340, aa352-360). [19] The SH region is the most variable part of the genome and is used for genotyping as well as for phylogenetic analysis of the virus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there was no association of certain polymorphisms in the NH and the SH gene with the development of this side effect [20]. …”
Section: Vaccination Against the Muvmentioning
confidence: 99%